2017
DOI: 10.21722/rbps.v18i2.15081
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento da gestante sobre o HIV e a transmissão vertical em São José do Rio Preto, São Paulo, Brasil

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
2
7
0
16
Order By: Relevance
“…In contrast to studies that found adequate knowledge of women, two recent researches that aimed to analyze the knowledge of seropositive pregnant women about the vertical transmission of HIV showed that mothers have a lack of knowledge regarding VT. However, both corroborate with the four studies of this review that health education should be an important tool in order to improve this knowledge (3)(4) .…”
Section: Use Of Soft Technologies and Educational Practices To Prevensupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast to studies that found adequate knowledge of women, two recent researches that aimed to analyze the knowledge of seropositive pregnant women about the vertical transmission of HIV showed that mothers have a lack of knowledge regarding VT. However, both corroborate with the four studies of this review that health education should be an important tool in order to improve this knowledge (3)(4) .…”
Section: Use Of Soft Technologies and Educational Practices To Prevensupporting
confidence: 86%
“…An article also showed that one of the most important actions to be developed by the nurse in the context of vertical transmission of HIV is health counseling, since it has allowed the improvement of HIV sensitization, prevention and control in pregnant women in Jamaica, besides the increase acceptance and empowerment to care for themselves and their children (19) . These data are corroborated by studies that emphasize the relevance of education in the continued health of HIV positive pregnant women, orchestrated to the level of understanding them, making them aware of their right to choose care with their body and advising on the importance and adverse effects of treatment, and that such effects are only phases that are necessary to be addressed as part of stages of coping with the disease (4,31) .…”
Section: Use Of Soft Technologies and Educational Practices To Prevenmentioning
confidence: 91%
See 2 more Smart Citations
“…etária de 15 a 49 anos de idade e 0,41% em mulheres, o que equivale a 251.584 mulheres infectadas. Um dado ainda mais preocupante é com relação à infecção em crianças com até 13 anos de idade, onde 84% dos casos são decorrentes de transmissão vertical(Jordão et al, 2016).Devido ao alto índice de transmissão vertical, o Ministério da Saúde preconiza a realização de exame anti-HIV na gestação com aconselhamento na primeira consulta de prénatal e, quando possível, a repetição da sorologia no início do 3º trimestre, sendo utilizados testes rápidos(Passos et al, 2013). Assim, o exame anti-HIV no pré-natal deve ser realizado através do consentimento da gestante após aconselhamento pré-teste, sendo o seu resultado entregue após aconselhamento pós-teste(Soares et al, 2013).Os indicadores e dados básicos do HIV/AIDS dos municípios brasileiros, do departamento de Doenças Sexualmente Transmissíveis (DST), AIDS e Hepatites Virais e da Secretária de Vigilância em Saúde, indicam que a região nordeste vem apresentando aumento do número de mulheres infectadas devido à existência de cidades sem tratamento adequado.Essa preocupação é maior quando o agravante é a mulher estar gestante, sendo que, no período de junho de 2003 a junho de 2015, foram notificados em Teresina-PI 363 casos de AIDS em gestantes, o que acarretou em 2,05 casos de bebês contaminados com AIDS em 1.000 recém-nascidos vivos.O uso do Geoprocessamento e de programas de computador de Sistemas de Informação Geográfica (SIG), que vêm sendo melhorados devido o abastecimento de informações em sites de agravos e serviços de saúde, permite observar mapas georreferenciados, com técnicas de sensoriamento remoto e análise espacial (disponibilizados no site do Instituto Brasileiro de Geografia e Estatística, IBGE) em conjunto com as características atribuídas, representando os valores de incidência por município em um estado, como exemplo (Chiaravalloti-Neto, 2017).…”
unclassified